Determinig the parameters of the acoustic system for the primary treatment of wool - Mykhailova, Lyudmyla; Kozak, Oleksandr; Kosulina, Natalia; Potapski, Pavel; Cherenkov, Aleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
We have studied the process of primary treatment of wool in order to remove soil and manure contaminants, vegetable impurities, fat, and sweat. The primary treatment of wool performs a key role in retaining the natural properties of wool fiber and makes it possible to obtain high-quality raw materials for textile industry. It was found in the course of research that the intensification of the processes of primary treatment of wool requires the application of acoustic oscillations. Acoustic oscillations act on the system wool‒washing solution. The system wool‒washing solution is in between grating conveyors. Conveyors form a grating of metal rods. To determine parameters of the acoustic system for the primary treatment of wool, we performed an analysis of three problems. The problems related to: the scattering of acoustic oscillations on a metal grating, on a layer of wool-washing solution, and combining the solutions to two problems into one using a scattering matrix method. Our study allowed us to define parameters for the system of primary treatment of wool with acoustic oscillations, which makes it possible to achieve greater effectiveness in cleaning wool compared to existing analogues. It was established in the course of theoretical and experimental studies that the washing of wool should be carried out at the following parameters of acoustic oscillations in a washing solution: frequency of the sound field is 1.1±0.1 kHz; the sound intensity is 1.1±0.01 W/cm2. In this case, the thickness of a layer of wool at the conveyor is 0.06±0.01 m; the motion speed of conveyor is 0.1 m/s; the number of converters per bath is 8±1 pieces. The application of optimal parameters in process of continuous washing of wool fibers in an aqueous solution makes it possible to obtain the residual fat on wool within 1.5 % of the amount of fat in the unwashed wool while GOST of Ukraine permits up to 2 %.